Решите уравнения y7 = 1,3, y=?
a1 = 0,9, a=?
0,04 + y 1,4, y=?
1,a = 1,31, a=?
3+x = 4,3 x=?
0,y = 0,4, y=?
b+0,03 = 0,23, b=?
b = 3,2 b=?
c5 = 0,8, c=?
1,2 + c 1,21,
0,5 + b = 2,5, b=?
a02 = 0,3, a=?
4,2 - y = 0,2 y=?
2=3,2, b=?
3,6 - b = 1,4, b=?
a - 3,2 = 0,8, a=?
3,a = 0,5, a=?
y + 0,03 = 1, y=?
0,y = 0,4, y=?
0,4 - x = 0,36, x=?
y' = 4*(x*e^2x)' =
4*( x' * e^2x + x*(e^2x)' ) =
4*( 1 * e^2x + x*(e^2x)*(2x)' ) =
4*( e^2x + x*(e^2x)*2 ) =
4 * e^2x + x*(e^2x)*8 =
4 * e^2x + 8 * x * e^2x
Б) y=ln (tg^2 (x/6))
y' = 1/tg^2 (x/6) * (tg^2 (x/6))' =
1/tg^2 (x/6) * 2*(tg^(2-1) (x/6)) * (tg (x/6))' =
1/tg^2 (x/6) * 2*(tg^1 (x/6)) * (tg (x/6))' =
1/tg^2 (x/6) * 2*(tg (x/6)) * (1/cos^2 (x/6)) * (x/6)' =
1/tg (x/6) * 2 * (1/cos^2 (x/6)) * (x/6)' =
1/tg (x/6) * 2 * (1/(cos^2 (x/6)) ) * (1/6) =
(2/6) * 1/tg (x/6) * (1/(cos^2 (x/6)) )=
(1/3) * 1/tg (x/6) * (1/(cos^2 (x/6)) )=
(1/3) * (cos (x/6)/sin (x/6)) * (1/(cos^2 (x/6)) )=
(1/3) * (1/sin (x/6)) * (1/(cos (x/6)) )=
(1/3) * (1/( (sin (x/6)) * (cos (x/6)) ) )=
(1/3) * ( 1/( (1/2)*sin(2x/6) ) ) =
(1/3) * (2/(sin(2x/6) ) ) =
(1/3) * (2/(sin(x/3) ) ) =
(2/3) * (1/(sin(x/3) ) ) =
2 / (3*sin(x/3))